ARABIC LANGUAGE LEARNING AT ISLAMIC BOARDING SCHOOL PPI 259 FIRDAUS, PANGALENGAN, BANDUNG - Uus Rustiman; Sutiono Mahdi (International Journal of Engagement and Empowerment, 2022)
Learning is a two-way conversation between teachers and students with the goal of improving students' ability to know, understand, and develop their abilities. This study falls under the category of qualitative research. After that, the data is processed utilizing the inductive thinking method. To use a qualitative descriptive analysis method to analyze the data, the author employs a variety of data collection techniques, including observation, documentation, and interviews. The findings revealed that students at Islamic Boarding School PPI 259 Firdaus Pangalengan, Bandung, learned Arabic using the nadzoriyatul wahdah/all in one system, which incorporated all aspects of Arabic learning. This is evident from the guidebook employed, Al-Arobiyyah Baina Yadaik, which employs the nadzoriyatul wahdah/ all-in-one approach in the application of Arabic language study at Pondok Pesantren PPI 259 Firdaus Pangalengan, Bandung Regency. Each level is taught in a distinct way, with different volumes, resources, and methods